Toxicological aspects of trans fat consumption over two sequential generations of rats: Oxidative damage and preference for amphetamine. Issue 1 (5th January 2015) - Kuhn, Fábio Teixeira; Trevizol, Fabíola; Dias, Verônica Tironi; Barcelos, Raquel Cristine Silva; Pase, Camila Simonetti; Roversi, Karine; Antoniazzi, Caren Tatiane de David; Roversi, Katiane; Boufleur, Nardeli; Benvegnú, Dalila Moter; Emanuelli, Tatiana; Bürger, Marilise Escobar
Highlights Rats received omega-3/-6 and trans fat (TF) from gestation over two generations. Pups from 2nd generation were also supplemented until adolescence. Omega-6 and TF groups showed higher anxiety and amphetamine (AMPH)-preference. TF group showed impairments in the antioxidant defense system in cortex/hippocampus. Brain incorporation of trans/n-6 fatty acids may facilitate drug addiction.